KEAUTENTIKAN ASESMEN PEMBELAJARAN: STUDI ANALISIS PRAKTEK ASESMEN GURU DI SEKOLAH KEJURUAN - Wahyuni, Luh Gede Eka (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2016)
ABSTRACT  This study was aimed at analyzing and describing the authenticity of assessment implementation by teachers in vocational school in Buleleng Regency. The analysis of assessment authenticity in this study was seen from teachers’ assessment planning and assessment implementation as well as how teachers and students perceive the assessment implementation. This study used exploratory method as the design involving 35 vocational English teachers and 35 classes of vocational students in Buleleng Regency. The data was gathered through document study, questionnaire, and interview and analyzed qualitatively. The results tend to point on a sufficient level of teachers’ assessment implementation. Its level was also found to be sufficient based on how teachers and students perceived its implementation. It was because most of the lesson plans designed by the teachers did not include relevant assessments yet to the expectation of the syllabus. The assessment instruments planned such as rubrik, blueprint, and test was found to be less appropriate. Although some assessments seemed to fulfill the criteria of authentic assessment well, inappropriateness of its implementation was still found. It indicated that the assessments implementation did not represent students’ competency yet as required in their real-world life.Keywords: assessment authenticity, teachers’ made assessment ABSTRAK Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan keotentikan pelaksanaan asesmen oleh guru di sekolah kejuruan di Kabupaten Buleleng. Analisis keotentikan asesmen dalam penelitian ini dilihat dari perencanaan asesmen guru dan pelaksanaannya serta persepsi guru dan siswa terhadap pelaksanaan asesmen. Exploratory method digunakan sebagai desain penelitian yang mengikutsertakan 35 guru Bahasa Inggris dan 35 kelas siswa kejuruan di Kabupaten Buleleng. Data dikumpulkan melalui studi dokumen, kuesioner, dan interview dan dianalisis secara kualitatif. Hasil analisis menunjukkan bahwa pelaksanaan asesmen guru berada pada katagori cukup otentik. Cukupnya tingkat keotentikan pelaksanaan asesmen guru juga ditemukan berdasarkan pada persepsi guru dan siswa terhadap pelaksanaannya.  Hal ini disebabkan oleh kurangnya perencanaan asesmen yang relevan dalam rancangan perencanaan pembelajaran (RPP) guru sehingga kurang mampu mencapai apa yang diminta dalam kurikulum.  Asesmen instrumen yang direncanakan dan dilaksanakan seperti rubrik, kisi-kisi, dan tes cenderung kurang sesuai untuk digunakan. Walaupun beberapa asesmen sudah memenuhi beberapa kriteria untuk dikatagorikan sebagai asesmen otentik, kekurangsesuain dari pelaksanaannya masih terjadi. Hal ini menunjukkan bahwa pelaksanaan asesmen guru, secara umum, belum mampu mewakili kompetensi siswa seperti apa yang diminta dalam dunia nyata.Kata kunci: keotentikan asesmen, asesmen guru